Effectiveness of distance teaching for autism spectrum disorder students during the COVID-19 pandemic - Riyadh Al Salahat; Aznan Che Ahmad (International Journal of Evaluation and Research in Education (IJERE), 2022)
This study examined the effectiveness and level of distance-teaching services provided to students with autism spectrum disorder in the United Arab Emirates, Emirate of Abu Dhabi (from a viewpoint of the teachers and parents). To achieve the study goals, the distance education services assessment tool was built in two forms. The data collection for this study was done by distributing online questionnaires to all participants. The results of the study indicated an assessment of distance-teaching services in a high level from the teachers' viewpoint with a total average (4.16 of 5), and the parent's viewpoint indicated their assessment of these services in a high level with a total average (4.18 of 5). The study suggested for future researchers to conduct more studiestargeting the challenges and difficulties during the distance-teaching for parents and teachers of students, include or limit other programs to assess the distance-teaching among parents and teachers of autism spectrum disorder students of severe degree.